2007
DOI: 10.1387/ijdb.062235js
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of Xenopus CRMP-4 in the developing nervous system

Abstract: KEY WORDS: Xenopus, primary neurogenesis, neurogenin, CRMP, NotchThe collapsin response mediator proteins (CRMPs) (also known as TOAD (turned on after division), Ulip (unc-33 like protein) and DRP (dihydropyrimidinase family) are a conserved family of cytosolic phosphoproteins highly expressed in the nervous system (Wang and Strittmatter, 1996). Even though the CRMPs exhibit more than 60% amino acid identity to the amidohydrolase family, they do not possess enzymatic activity (Wang and Strittmatter, 1997).The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Similar to the zebrafish (Lukowski et al, 2006), IA1 is strongly expressed in the primary nervous system. By in situ hybridization, IA1 transcripts are first detected at stage 11-11.5 in precursors of the primary neurons and of the trigeminal placodes, after the bHLH gene Ngnr1 (Ma et al, 1996) already activated at stage 10.5 and before ElrC and terminal differentiation markers such as CRMP-4 (Carruthers et al, 2003;Souopgui et al, 2007) (Fig. 1A,B and data not shown).…”
Section: Ia1 Is Highly Expressed In the Nervous System Including Antmentioning
confidence: 90%
“…Similar to the zebrafish (Lukowski et al, 2006), IA1 is strongly expressed in the primary nervous system. By in situ hybridization, IA1 transcripts are first detected at stage 11-11.5 in precursors of the primary neurons and of the trigeminal placodes, after the bHLH gene Ngnr1 (Ma et al, 1996) already activated at stage 10.5 and before ElrC and terminal differentiation markers such as CRMP-4 (Carruthers et al, 2003;Souopgui et al, 2007) (Fig. 1A,B and data not shown).…”
Section: Ia1 Is Highly Expressed In the Nervous System Including Antmentioning
confidence: 90%
“…Dihydropyrimidinase‐like proteins were first characterized as phosphoproteins that were highly expressed in the developing nervous system and DPYSL family members regulate neurite outgrowth, axonal guidance and cell differentiation . Recently, a study on the roles of DPYSLs in vivo indicated that during neurulation in zebrafish DPYSL3 was required for proper positioning of neural crest cells in the developing spinal cord .…”
Section: Discussionmentioning
confidence: 99%
“…Dihydropyrimidinase-like proteins were first characterized as phosphoproteins that were highly expressed in the developing nervous system and DPYSL family members regulate neurite outgrowth, axonal guidance and cell differentiation. (13,29,30) Recently, a study on the roles of DPYSLs in vivo indicated that during neurulation in zebrafish DPYSL3 was required for proper positioning of neural crest cells in the developing spinal cord. (31) This report highlights the importance of DPYSL3 in differentiation of neural crest cells and supports our findings that DPYSL3 expression may be important during the differentiation of neural crest-derived NB tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Digoxigenin-labeled antisens RNA probes for gad1, VGlut1 [56], TH [53], tubb2b [48], Bru [57], dpysl3 [58], Ptf1a [45] and Ascl1 [50] were generated according to the manufacturer’s instruction (Roche). Whole mount in situ hybridization [59] and double fluorescent in situ hybridizations on cryosections [60] were carried out as previously described.…”
Section: Methodsmentioning
confidence: 99%